An electrochemical reduction process for the recovery of copper powder from a refinery effluent stream - Bezuidenhout, Chandon (Department of Chemical Engineering, 2017)
In recent years a significant amount of research has gone into the development of a feed pretreatment process for the concentrate refined at Anglo American Platinum's Precious Metals Refiners (PMR). Such a process has the potential to significantly simplify the downstream refining process and reduce the number of unit processes required for purification. One of the considered options involves a high temperature oxidative roast process followed by a high temperature hydrochlorination process to volatilise base metal chlorides and other impurities. The resulting precious group metal (PGM) concentrate is cleaner and thus requires significantly less process steps to final product. The off-gas from hydrochlorination contains predominantly silver, copper, nickel and iron. This off-gas undergoes a quench-scrub to condense the base metal chlorides. The quench-scrub liquor undergoes a dechlorination process with sulfuric acid to precipitate AgCl(s). The filtrate from this process then undergoes an electrochemical reduction process to recover copper metal concentrate. The objectives of this study were to: i. Determine the operating conditions for an electrochemical reduction process aimed at recovering copper as a copper powder from a sulfuric acid stream containing copper, nickel and iron. ii. Develop a conceptual flowsheet for a batch electrochemical process and estimate the capital cost and operating cost.